Eudaimonic entertainment as new Enlightenment: Critical thinking as a mind-set effect of narratives - Bilandzic, Helena; Blessing, Janine Nadine (Frontiers in Communication, 2022)
We propose to extend the theoretical concept of eudaimonia as a media effect with critical thinking as a mind-set effect. Critical thinking as a mind-set effect means that media narratives can stimulate viewers and readers to think critically in any situation, even outside of the exposure situation and applied to other topics. It denotes a generally heightened critical attitude or “mind-set” to approach issues and situations by taking different pieces of information into account, weighing and analyzing them, developing one’s own arguments and drawing conclusions. People with this mind-set try to be well-informed, use credible sources and observations, are alert for alternatives, open-minded, maintain and change views according to evidence, and are motivated to hold accurate beliefs. In this article, we provide a theoretical elaboration of the idea of critical thinking as a mind-set effect, and connect it to traditions of Enlightenment literature as well as theoretical approaches on narrative effects. We also present data from a qualitative pilot study using the film “Don’t look up” to explore the potential of such an extension of eudaimonic entertainment. Finally, we discuss implications of introducing critical thinking as a mind-set effect for narrative persuasion.